The Effect of Different Curing Methods on the Compressive Strength of Eggshell Concrete - Tan, Yeong Yu; Doh, Shu Ing; Chin, Siew Choo (Informatics Publishing Limited, 2017)
The work assesses the effect of different curing conditions on the compressive strength of the eggshell concrete. Two different qualities of the eggshell powder were used to make concrete with 0.45 water/cement ratio. The eggshell powders were treated as partial cement replacement of 5%, 10%, 15% and 20%. The concrete cube specimens (100 x 100 x 100) mm were exposed to two different environments (full water curing and open-air curing) for 1, 7 and 28 days. The results exhibit that the initial strength growth for the compressive strength with increases with the percentage of the replacement up to 15%, being this behaviour more evident for the full water curing environment up to 67.53%. The 28- days compressive strength of the eggshell concrete for full water curing and open air curing were found at 49.23 MPa and 46.34 MPa respectively. However, the concrete specimens lost 24.7% and 34.83% when the eggshell powder replace up to 20% of the partial cement replacement for full water curing and open air curing. Thus, water curing is found to be more suitable compared to to open air curing.